Joint statistics of cosmological constant and SUSY breaking in flux vacua with nilpotent Goldstino - Michele Cicoli; Matteo Licheri; Anshuman Maharana; Kajal Singh; Kuver Sinha (Journal of High Energy Physics, 2023)
Abstract We obtain the joint distribution of the gravitino mass and the cosmological constant in KKLT and LVS models with anti-D3 brane uplifting described via the nilpotent goldstino formalism. Moduli stabilisation (of both complex structure and Kähler moduli) is incorporated so that we sample only over points corresponding to vacua. Our key inputs are the distributions of the flux superpotential, the string coupling and the hierarchies of warped throats. In the limit of zero cosmological constant, we find that both in KKLT and LVS the distributions are tilted favourably towards lower scales of supersymmetry breaking.